PROGRAM TAMRINUL KHITOBAH TERHADAP SANTRI PONDOK PESANTREN AN-NURIYAH BONTOCINI KABUPATEN JENEPONTO (Fakultas Dakwah dan Komunikasi, 2021)
This study discusses the Tamrinul Khitobah program for santri at An-Nuriyah Bontocini Islamic Boarding School, Jeneponto regency. The purpose of this study was to see how the process implementing the Tamrinul Khitobah at the An-Nuriyah Bontocini Islamic Boarding school, and to see the responses of the students to their preaching abilities in the Tamrinul Khitobah program at the An-Nuriyah Bontocini Islamic Boarding school. The Tamrinul Khitobah program is a form of coaching carried out by the pesantren in training santri to preach before the students enter the community, the process of implementing the Tamrinul Khitobah program is carried out routinely every Friday night, the time takes place between evening prayer and evening prayer time. The Tamrinul Khitobah is organized directly by the coaches of male and female dormitories, the schedule is arranged by the boarders and assisted by all members of the intra pesantren organization (OSIP), every Friday night the program is carried out at the pesantren mosque, and is divided into 2 to 4 groups, and 10 to 15 students deliver their da’wah material in front of the coach and other students. The da’wah material used by students in the Tamrinul Khithobah program is in 7 languages, namely English, Arabic, regional, Indonesian, Japanese, Mandarin, and French. The response of the students to the Tamrinul Khitobah program can be concluded that Tamrinul Khitobah has a big influence on students because it teaches more confidence, better rhetoric, good morals, dares to stand in front of the community, dares to be a leader, and learn to preach. Use foreign languages according to their respective abilities.